Taking advantage of cellular uptake of ferritin nanocages for targeted drug delivery - Tesarova, Barbora; Musilek, Kamil; Rex, Simona; Heger, Zbynek (Journal of controlled release, 2020)
The search for ideal nanocarrier, which could be rapidly translated to clinical practice, isstill ongoing over the past few decades. However, many reviews are focused onimportant properties of ideal nanocarrier, including long circulation, high internalization efficiency ofadrug, surface charge of nanocarrier or the ability to encapsulate high amount of a drug. Indeed, theability to encapsulate wide variety of drugs, noimmunogenicity, biodegradability ornanocarrier monodispersity are very important aspects, therefore they are discussed in this review. The use of nanocarrier formulations able to innately form self-assembly cages ofuniform size and shape, employing protein-based structures naturally present inhuman body, seems to be very promising. Typical protein nanocarrier disposing all the above mentioned characteristics is represented by ferritin (FRT). Hence, the presented review provides detailed characterization of FRT structure, including its disassembly and reassembly properties, which are crucial for encapsulation ofdrugs, together with possibilities of active targeting, exploiting both the innate affinities of FRT nanocages towards selected receptors and the plethora of surface functional groups that can be used to attach a variety of targeting ligands. Finally, we discuss theopportunities of cutting-edge approaches to FRT-based nanotherapy and the challenges that must be overcome or avoided.
Keywords: léčivé přípravky; Humans; Pharmaceutical Preparations; Nanomedicine; Ferritins; ferritiny; Drug Delivery Systems; lidé; Theranostics; Ferritin; zvířata; Biocompatibility; biologický transport; lékové transportní systémy; nádorové buněčné linie; Drug delivery; Animals; Cell Line, Tumor; Biological Transport